Reverse modeling of the human mandible 3D geometric model - Mitić, Jelena; Vitković, Nikola; Manić, Miodrag; Trajanović, Miroslav; Petrović, Sladjana; Arsić, Stojanka (Vojnosanitetski pregled, 2021)
Background/Aim. The geometry of each bone in the human skeletal system is unique. The aim of this research was to present application of a new method, method of anatomical features (MAF), for the creation of the geometrical model (surface and solid) of the human mandible. Methods. The method was based on Referential Geometrical Entities (RGEs) which have been defined on mandible polygonal model in accordance with anatomical properties of the mandible. Polygonal model was created over the input data (anatomical landmarks of the mandible) acquired from computed tomography scans. For the creation of computer-aided design (CAD) models in CATIA software, referential geometrical entities were defined according to the bone geometry and morphology features. Results. Definition of B-spline curves was performed on the body and on the ramus of the mandible. In this way, it was possible to create the geometrically accurate and anatomically correct three-dimensional geometric (surface and solid) models. The accuracy of the obtained surface model was tested through comparison with the geometry of the original bone model. Conclusion. Compared to the previously applied methods for creating geometric models, MAF provides more satisfactory results, and in some cases even better.
Keywords: mandible; methods; models, anatomic; printing, three-dimensional; technology, medical; tomography, x-ray computed